Crisis Communication of Public Relations Nijisanji EN on Corporate Image (Content Analysis on Nijisanji EN's YouTube Account in Addressing the Case of Vtuber Selen Tatsuki's Dismissal) - Devi, Deva Mouliyana; Setyansih, Rila; Febrianti, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2025)
A crisis is an unpredictable phenomenon that can arise from internal company issues, such as the case of Selen's dismissal by Nijisanji, which operates under Anycolor Inc. This dismissal triggered various reactions from the fan community, ranging from support for Selen to criticism of Nijisanji's management policies. The primary cause of this dismissal was the internal dispute between Selen and Nijisanji. In examining this issue, the author employs qualitative descriptive research with a content analysis method. The qualitative content analysis method allows for flexibility in data collection related to the case under study. By using content analysis and Situational Crisis Communication Theory, the author aims to study how Nijisanji EN responds to crises. The results of this study indicate that the crisis experienced by Nijisanji EN falls into the category of a Preventable Crisis. The conclusion drawn is that the management's inability to control Nijisanji's crisis communication response led to the company suffering significant losses due to a series of crucial and difficult-to manage crises.